Study of coverage of confidence intervals for the standardized mortality ratio in studies with missing death certificates - Timkova, Jana; Kotik, Lukas; Tomasek, Ladislav (Statistics in medicine, 2017)
This paper assesses the coverage probability of commonly used confidence intervals for the standardized mortality ratio (SMR) when death certificates are missing. It also proposes alternative confidence interval approaches with coverage probabilities close to .95. In epidemiology, the SMR is an important measure of risk of disease mortality (or incidence) to compare a specific group to a reference population. The appropriate confidence interval for the SMR is crucial, especially when the SMR is close to 1.0 and the statistical significance of the risk needs to be determined. There are several ways to calculate confidence intervals, depending on a study characteristics (ie, studies with small number of deaths, studies with small counts, aggregate SMRs based on several countries or time periods, and studies with missing death certificates). This paper summarizes the most commonly used confidence intervals and newly applies several existing approaches not previously used for SMR confidence intervals. The coverage probability and length of the different confidence intervals are assessed using a simulation study and different scenarios. The performance of the confidence intervals for the lung cancer SMR and all other cancer SMR is also assessed using the dataset of French and Czech uranium miners. Finally, the most appropriate confidence intervals to use under different study scenarios are recommended.
Keywords: standardized mortality ratio; missing certificates; simulation study; Models, Statistical; Mortality; uranium miners; nádory plic; lidé; Death Certificates; statistické modely; confidence intervals; Probability; Francie; mortalita; úmrtní listy; interval spolehlivosti; Confidence Intervals; pravděpodobnost; Risk Factors; aggregation; nemoci z povolání; Czech Republic; rizikové faktory; France; Lung Neoplasms; Česká republika; Occupational Diseases; Uranium; coverage; uran; profile likelihood; Humans